Evaluation of Prognostic response in HIV positive patients after Antiretroviral Therapy - NadyaUsman,MuhammadAbdulRehman,MuhammadBilalGhafoor,MuhammadAliMalik,MuhammadShoaibKhan,AjmalShahBukhari, NadyaUsman,MuhammadAbdulRehman,MuhammadBilalGhafoor,MuhammadAliMalik,MuhammadShoaibKhan,AjmalShahBukhari (Journal of Rawalpindi Medical College, 2020)
Objective: The present study was aimed to monitor the prognostic response of antiretroviral therapy in HIV positive patients. Methodology: The study was conducted on confirmed HIV positive patients registered at HIV treatment and care centre, PIMS. Islamabad from January 2013 to December 2015.. Among all HIV positive patients,276 adult cases were selected. There were 263 patients on first-line antiretroviral (ARV) therapy and 13 patients were shifted to 2nd line ARV therapy.CD4 cell counts and viral load (Polymerase chain reaction) monitoring was done after one year of starting ARV therapy. Results: Out of 276 adult patients, 75%(n=207) were male and 25%(n=69) were females. Among 276 adult cases, 95.3% (n=263) patients were on first line ARV therapy. Patients on first line ARV therapy showed good prognostic response. There were 15.5%(n=40) patients having CD4+cells less than 350cells/µL. There were 84.5%(n=223) patients having CD4 +cells count greater than 350cells/µL There were 69%(n=182) patients having viral load <50copies/ml and 31%(n=81) patients who had viral load >50copies/ml. Conclusion: First line ARV therapy given to HIV positive patients proved itself best both in respect of increasing the immunity of HIV positive patients by increasing the number of CD4 cells and also results in effective viral load suppression.